NILAI PENDIDIKAN AKHLAKDALAM AL-QUR’AN SURAT AL-BAQARAH AYAT 153-157 (STUDI PUSTAKA TAFSIR AL-AZHAR) - Mandri Saputra Rustin; Andrizal Andrizal; Helbi Akbar (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Indeed moral education is an important part of the substance of Islamic education. Rasulullah SAW. sent by Allah Almighty. to become an apostle with the task of perfecting the glory of humanity. Without morals, human life is no different from animals. This study aims to determine and examine how the value of moral education in the Qur'an Al-Baqarah verse 153-157. The questions that will be answered through this research are: 1) Knowing the value of moral education in Al-Qur'an Surat Al-Baqarah verses 153-157 and 2) Knowing the Implementation of the Value of Moral Education in Al-Qur'an Surat Al-Baqarah verse 153- 157 in human life. To answer these questions, this study uses the type of library research, that is, research by collecting data that is related to the object of research, both primary data (Al-Qur'an Surat Al-Baqarah Verses 153-157), Secondary ( translations and interpretations of the Surah Al-Baqarah verses 153-157), as well as tertiary (other books concerned with research are sought from literature sources). The technical analysis of data uses the Thematic Interpretation method, description and analysis. This research shows that the value of moral education contained in Al-Qur'an Qur'an Al-Baqarah 153-157 is needed in daily life. The value of moral education in the Qur'an Al-Baqarah verse 153-157, namely: the Value of Patient Education. Implementation of the value of moral education in the Qur'an Al-Baqarah verse 153-157 is by applying the value of moral education to daily life whether it is fellow brothers, family or community, that this patient moral education must be applied in every person.